2023
DOI: 10.31788/rjc.2023.1618053
|View full text |Cite
|
Sign up to set email alerts
|

ULTRASONICALLY ASSISTED SYNTHESIS OF CHROMEN-2- ONE-1,2,3-TRIAZOLES AND In-vitro ANTICANCER ACTIVITY

Abstract: Synthesis of new series of chromen-2-one-1,2,3-Triazoles (6a-6j) was reported using the help of key methods such as [3+2]-cycloaddition and ultrasound. All compounds were further evaluated for their in vitro anticancer activity profile in three human cancer cell lines MCF-7(breast), A-549 (lungs), and HeLa (cervical). Among all, three compounds namely 6c, 6f, and 6j showed the most promising activity against three lines, when compared with the etoposide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…3.08 µM) and was superior to that of cisplatin (IC 50 : 45.33 µM). [97][98][99] Oxime can also serve as a linker, and 1,2,3-triazole-oximecoumarin hybrids 74 (IC 50 : 29.26-53.28 µM, MTT assay) were active against MCF-7 breast cancer cells. [100] The SAR elucidated that the electron-donating group at ortho-position or electron-withdrawing that fluoro on the phenyl ring was favorable to the activity.…”
Section: 23-triazole-azole Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…3.08 µM) and was superior to that of cisplatin (IC 50 : 45.33 µM). [97][98][99] Oxime can also serve as a linker, and 1,2,3-triazole-oximecoumarin hybrids 74 (IC 50 : 29.26-53.28 µM, MTT assay) were active against MCF-7 breast cancer cells. [100] The SAR elucidated that the electron-donating group at ortho-position or electron-withdrawing that fluoro on the phenyl ring was favorable to the activity.…”
Section: 23-triazole-azole Hybridsmentioning
confidence: 99%
“…Further study revealed that the amide fragment at the N‐1 position of 1,2,3‐triazole moiety was not essential for the activity, and hybrid 70 (IC 50 : 3.12 µM, MTT assay) was not inferior to doxorubicin (IC 50 : 2.63 µM) against MCF‐7 breast cancer cells; [ 96 ] extension of the carbon spacer between 1,2,3‐triazole and coumarin moieties was tolerated, and hybrids 71 (IC 50 : 2.85 µM, MTT assay), 72a,b (IC 50 : 4.15 and 3.82 µM, MTT assay), and 73 (IC 50 : 2.48 µM, MTT assay) showed potent antiproliferative activity against MCF‐7 breast cancer cells, and the activity was comparable to that of etoposide (IC 50 : 3.08 µM) and was superior to that of cisplatin (IC 50 : 45.33 µM). [ 97–99 ]…”
Section: 23‐triazole‐coumarin/flavonoid Hybridsmentioning
confidence: 99%